Complex interactions between bacteria and haemosporidia in coinfected hosts: An experiment - Reinoso‐Pérez, María Teresa (Ecol Evol, 2020)
1. Hosts are typically coinfected by multiple parasite species whose interactions might be synergetic or antagonistic, producing unpredictable physiological and pathological impacts on the host. This study shows the interaction between Plasmodium spp. and Leucocytozoon spp. in birds experimentally infected or not infected with Mycoplasma gallisepticum. 2. In 1994, the bacterium Mycoplasma gallisepticum jumped from poultry to wild birds in which it caused a major epidemic in North America. Birds infected with M. gallisepticum show conjunctivitis as well as increased levels of corticosterone. 3. Malaria and other haemosporidia are widespread in birds, and chronic infections become apparent with the detectable presence of the parasite in peripheral blood in response to elevated levels of natural or experimental corticosterone levels. 4. Knowing the immunosuppressive effect of corticosterone on the avian immune system, we tested the hypothesis that chronic infections of Plasmodium spp. and Leucocytozoon spp. in house finches would respond to experimental inoculation with M. gallisepticum as corticosterone levels are known to increase following inoculation. 5. Plasmodium spp. infection intensity increased within days of M. gallisepticum inoculation as shown both by the appearance of infected erythrocytes and by the increase in the number and the intensity of positive PCR tests. 6. Leucocytozoon spp. infection intensity increased when Plasmodium spp. infection intensity increased, but not in response to M. gallisepticum inoculation. Leucocytozoon spp. and Plasmodium spp. seemed to compete in the host as shown by a negative correlation between the changes in their PCR score when both pathogens were present in the same individual. 7. Host responses to coinfection with multiple pathogens measured by the hematocrit and white blood cell count depended on the haemosporidian community composition. Host investment in the leukocyte response was higher in the single‐haemosporidia‐infected groups when birds were infected with M. gallisepticum. 8. A trade‐off was observed between the immune control of the chronic infection (Plasmodium spp./Leucocytozoon spp.) and the immune response to the novel bacterial infection (M. gallisepticum).